Adeno-associated virus-vectored delivery of HIV biologics: the promise of a “single-shot” functional cure for HIV infection - Patricia A. Hahn; Mauricio A. Martins (Journal of Virus Eradication, 2023)
The ability of immunoglobulin-based HIV biologics (Ig-HIV), including broadly neutralizing antibodies, to suppress viral replication in pre-clinical and clinical studies illustrates how these molecules can serve as alternatives or adjuncts to antiretroviral therapy for treating HIV infection. However, the current paradigm for delivering Ig-HIVs requires repeated passive infusions, which faces both logistical and economic challenges to broad-scale implementation. One promising way to overcome these obstacles and achieve sustained expression of Ig-HIVs in vivo involves the transfer of Ig-HIV genes to host cells utilizing adeno-associated virus (AAV) vectors. Because AAV vectors are non-pathogenic and their genomes persist in the cell nucleus as episomes, transgene expression can last for as long as the AAV-transduced cell lives. Given the long lifespan of myocytes, skeletal muscle is a preferred tissue for AAV-based immunotherapies aimed at achieving persistent delivery of Ig-HIVs. Consistent with this idea, recent studies suggest that lifelong immunity against HIV can be achieved from a one-time intramuscular dose of AAV/Ig-HIV vectors. However, realizing the promise of this approach faces significant hurdles, including the potential of AAV-delivered Ig-HIVs to induce anti-drug antibodies and the high AAV seroprevalence in the human population. Here we describe how these host immune responses can hinder AAV/Ig-HIV therapies and review current strategies for overcoming these barriers. Given the potential of AAV/Ig-HIV therapy to maintain ART-free virologic suppression and prevent HIV reinfection in people living with HIV, optimizing this strategy should become a greater priority in HIV/AIDS research.